Sexual Behavior Among Injection Drug Users and Potential for HIV Spread to Non-Injectors in A Western Indian City - Chavan, L B; Patel, Prakash; Modi, Bhavesh; Undhad , Ashwin (National Journal of Community Medicine, 2010)
Objective: To examine the risk of sexual transmission of HIV from IDUs to noninjecting populations in Surat city. Methods: In late 2008, 157 IDUs were recruited using snow ball sampling originating from injecting sites. Trained interviewers administered a questionnaire focusing on sexual behavior, and HIV-related knowledge. Results: Over 97 percent of IDUs were sexually active, 48% reported multiple partners, and 29% had bought sex from a female sex worker in the preceding 3 months. Proportion of IDUs who had never used condom was 69%. Conclusions: The potential for the sexual spread of HIV from IDUs to nanoinjectors is extremely high in the city. Interventions are urgently needed to increase condom use among IDUs.